Efficient photocatalysis of organic dyes under simulated sunlight irradiation by a novel magnetic CuFe2O4@porphyrin nanofiber hybrid material fabricated via self-assembly. (1st December 2020) - La, D. Duong; Tran, Chinh V.; Hoang, Nhung T.T.; Doan Ngoc, M. Duyen; Nguyen, T.H. Phuong; Vo, H. Tung; Ho, P. Hien; Nguyen, T. Anh; Bhosale, Sheshanath V.; Nguyen, X. Cuong; Chang, S. Woong; Chung, Woo J.; et al.
Graphical abstract: Highlights: CuFe2 O4 @tetracarboxy-porphyrin nanofiber hybrid materials were synthesized. Hybrid material exhibited good photoenergy-harvesting from solar fuel. Hybrid material was magnetically separable and recyclable. Self-assembly was used to produce efficient photocatalysts for water splitting. Rhodamine B degradation mechanism using composite material is proposed. Abstract: The main aim of this study was to synthesize an innovative magnetic CuFe2 O4 @porphyrin nanofiber hybrid material via one-step re-precipitation self-assembly of freebase-tetracarboxy-porphyrin (TCPP), in the presence of CuFe2 O4 nanoparticles. The resultant hybrid materials were thoroughly characterized using scanning electron microscopy, energy-dispersive X-ray mapping, X-ray diffractometry, and Fourier-transform infrared, and UV–vis spectroscopy. Results showed well-integration of CuFe2 O4 nanoparticles into TCPP nanofiber network, with the average size of CuFe2 O4 being less than 100 nm and diameter and length of TCPP aggregate being approximately 20 nm and several µm, respectively. The as-prepared hybrid material possessed strong magnetic properties with a saturated magnetization value of approximately 25 emu/g. This photocatalyst was highly efficient in the removal of rhodamine B (RhB) dye, with the rate constant reaching 2.1 × 10 −2  min −1 . This paper describes in detail a plausible photocatalytic mechanism for RhB removal by CuFe2 O4 @porphyrin nanofiber hybrid material.